Functionalization of sawdust biochar using Mg-Fe-LDH and sodium dodecyl sulfonate enhanced its stability and immobilization capacity for Cd and Pb in contaminated water and soil - Xin Pan; Shaoping Kuang; Xiao Wang; Habib Ullah; Zepeng Rao; Esmat F. Ali; Qumber Abbas; Sang Soo Lee; Sabry M. Shaheen (Biochar)
Abstract The increased contamination of potentially toxic element (PTE) has posed remarkable ecological risks to environment. Application of functionalized biochar for the remediation of PTE contaminated water and soils are of great concern, and effective strategies are urgently needed to enhance the removal capacity of biochar for PTE. As a novel surface modification technology, the effect of layered double hydroxides (LDH) and sodium dodecyl sulfonate (SDS) on the remediation capacity of biochar for PTE polluted soils and water remains unclear. Sawdust biochar (SB) was coated with Mg and Fe to synthesize the Mg-Fe-LDH functionalized biochar (MFB); thereafter, the MFB was mixed with SDS solution to synthesize the organic-Mg-Fe-LDH biochar (MSB). The potential of SB, MFB, and MSB for remediation of Cd and Pb contaminated soil and water was evaluated in terms of adsorption capacity, immobilization efficiency, and stability. Loading of Mg-Fe-LDH into SB, along with SDS treatment created a regular micro-nano hierarchical structure and enhanced the surface roughness, aromaticity, and hydrophobicity of MSB as compared to SB. MSB exhibited a significantly higher maximum adsorption capacity (mg g−1) for water Pb (405.2) and Cd (673.0) than MFB (335.9 for Pb and 209.0 for Cd) and SB (178.2 for Pb and 186.1 for Cd). MSB altered the soluble fraction of Cd/Pb to the residual fraction and thus significantly decreased their mobilization in soil. The higher removal/immobilization efficiency of MSB could be attributed to its alkalinity, and the enhanced synergistic interactions including surface precipitation, ion exchange, complexation, and hydrogen bonding. The resistance to carbon loss by H2O2, thermal recalcitrance index R 50, and degree of graphitization in MSB were significantly improved compared to SB, indicating a more stable carbon fraction sequestered in MSB following aging in soil. These results indicate that MSB could be used for remediation of Cd and Pb contaminated soil and water. Graphical Abstract